History of the Indian Mutiny of 1857-58. - Kaye, Sir John (The History of the Indian Mutiny of 1857-58, 2013)
Volume III of VIBest edition of the standard work (with analytical index in Vol. VI)Contemporary review from the Athenaeum:It only be remarked that Colonel Malleson wields his pen with so much skill that while giving a realistic account of all important operations, passing over no really noteworthy act of talent or heroism, and acutely criticising everything which demands criticism, he abstains from overlaying his narrative with details which would have increased the bulk of his book beyond all reason. Another characteristic of Colonel Malleson is that he never hesitates to condemn conduct of which he disapproves or to draw attention to errors which he conceives were committed, whatever the rank or position of those who are the objects of his criticism. The result is that many of the actors in the drama will find their laurels somewhat injured, while others, who from official prejudice have not yet received full credit for their exploits, obtain from the author due praise for their services. The rewards given for the Mutiny were liberal, but it is distressing to find that some of them were undeserved, while on the other hand, many able and gallant men have received no recognition at all ... There are many highly-placed officials whose fame is sadly tarnished by the frank, truthful criticisms of the fearless, uncompromising author of the book before us.